Sistema de detección de mamíferos en el área ecoturística del bosque protector Murocomba - Marcillo Yépez, Arturo Adrian (2024)
The project "Detection System for Mammals in the Ecotourism Area of Bosque Protector Murocomba" aims to develop an efficient technological tool for monitoring and conserving mammal species in this biodiversity-rich protected area. This system employs camera traps and a CCTV network combined with a web application for image recognition, using training models based on specific datasets. The proposed solution will enable the precise capture of data on the presence, distribution, and behavior of species, contributing to the sustainable management of the ecosystem. The research addresses the lack of an adequate monitoring system that limits the ability to respond to threats such as poaching and habitat destruction. Additionally, it seeks to promote environmental education by providing real-time information to area visitors. The study's findings are expected to improve conservation strategies, enhance understanding of local biodiversity, and strengthen national ecosystem preservation efforts in Ecuador. This integrative approach, which combines automated monitoring techniques and data analysis, offers a replicable model for other protected areas.